Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
7/5 - a/4 = 13/20
a/4 = 7/5 - 13/20
a/4 = 3/4
=> a = 3
Vậy a = 3
4/5 x 3/4 - 3/10
= 12/20 - 3/10
= 12/20 - 6/20
= 6/20
= 3/10
\(\dfrac{3}{4}.\dfrac{2}{3}-\dfrac{1}{6}.\dfrac{3}{4}-\dfrac{3}{4}.\dfrac{1}{2}\)
= \(\dfrac{3}{4}.\left(\dfrac{2}{3}-\dfrac{1}{6}-\dfrac{1}{2}\right)\)
= \(\dfrac{3}{4}.0\)
= 0
\(\dfrac{3}{4}\cdot\dfrac{2}{3}-\dfrac{1}{6}\cdot\dfrac{3}{4}-\dfrac{3}{4}\cdot\dfrac{1}{2}\)
\(=\dfrac{3}{4}\left(\dfrac{2}{3}-\dfrac{1}{6}-\dfrac{1}{2}\right)\)
\(=\dfrac{3}{4}\cdot\left(\dfrac{4}{6}-\dfrac{1}{6}-\dfrac{3}{6}\right)\)
=0
\(\frac{1}{3}x\)\(\frac{1}{2}-\frac{1}{5}x\)\(\frac{1}{2}\)
=(\(\frac{1}{3}-\frac{1}{5}\)) x \(\frac{1}{2}\)
=\(\frac{2}{15}x\)\(\frac{1}{2}\)
=\(\frac{1}{15}\)
1/3 * 1/2 - 1/5 * 1/2
= (1/3 + 1/5) * 1/2
=8/15*1/2
=4/15
1 - 3/4 = 4/4 - 3/4 = 1/4
Chúc bạn học tốt.
😁😁😁
\(=\frac{1}{4}\)